(untitled) - Wade, L. G. (New York, 2006)
Features SpartanViewTM and SpartanBuildTM software. This workbook includes a software tutorial and numerous challenging exercises students can tackle to solve problems involving structure building and analysis using the tools included in the two pieces of Spartan software. Included are the molecular model files for the activities. This is sold at the instructor's discretion and is free when packaged with the text.
Keywords: Chemistry, organic